ChemInform Abstract: Metal Free C—H Functionalization of Diazines and Related Heteroarenes with Organoboron Species and Its Application in the Synthesis of a CDK Inhibitor, Meriolin 1. Issue 37 (August 2016) - Thatikonda, Thanusha; Singh, Umed; Ambala, Srinivas; Vishwakarma, Ram A.; Singh, Parvinder Pal
Abstract: A broad range of hetarenes is coupled with various aryl and hetaryl boronic acids to form the products in moderate yields.